2015
DOI: 10.1111/jbi.12616
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stratification of moths across elevation and latitude

Abstract: Aim There is little consensus as to whether stratification of arthropods between canopy and understorey in tropical and subtropical forests is commonplace and if the magnitude of stratification changes across different elevations and latitudes. We investigated broad-scale patterns of vertical stratification of moths collected from extensive cross-continental fieldwork in a variety of forest types, climates, elevations, latitudes and areas with differing biogeographical history.Location Tropical and subtropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…It is presumed that this layering allows for greater species coexistence, so verticality should also influence biogeographical patterns via its interaction with the physical and climatic environments (MacArthur and MacArthur 1961). Our findings corroborate this long-standing hypothesis in ecology, which previously has only been tested at local to regional scales (Bernard 2001, Vieira and Monteiro 2003, Scheffers et al 2013, Ashton et al 2016, Marques et al 2016). Arboreality coincides with species richness (Fig.…”
Section: Arboreality and Latitudinal Biodiversity Gradientssupporting
confidence: 85%
See 1 more Smart Citation
“…It is presumed that this layering allows for greater species coexistence, so verticality should also influence biogeographical patterns via its interaction with the physical and climatic environments (MacArthur and MacArthur 1961). Our findings corroborate this long-standing hypothesis in ecology, which previously has only been tested at local to regional scales (Bernard 2001, Vieira and Monteiro 2003, Scheffers et al 2013, Ashton et al 2016, Marques et al 2016). Arboreality coincides with species richness (Fig.…”
Section: Arboreality and Latitudinal Biodiversity Gradientssupporting
confidence: 85%
“…First, as environments become more structurally complex, arboreality becomes a beneficial attribute provided by morphological specializations for perching, nesting and foraging on branches of trees (Hildebrand andGoslow 2001, Gomes et al 2009). Arboreality has been shown to play an important role in determining localized biogeographic patterns of species richness, suggesting that vertical stratification of species within forest canopies enable greater species coexistence (MacArthur and MacArthur 1961, Corlett and Primack 2011, Scheffers et al 2013, Ashton et al 2016). If increased vegetation structure leads to increased vertical stratification, we would infer that the greatest levels of arboreality would occur in the tropics, because habitat heterogeneity is highest at the equator and lowest at the poles (Simard et al 2011, Crowther et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the pattern of stratification is in line with Hirao et al (2009) and most studies in the tropics (Intachat and Holloway (2000); Schulze et al (2001); Brehm (2007) and Ashton et al (2015)). Hacker and M€ uller (2008) however, found a much higher number of species at the ground level, than at higher strata in a German forest.…”
Section: Discussionsupporting
confidence: 75%
“…Different studies in the tropics have demonstrated different degrees of vertical stratification in moth communities: Intachat and Holloway (2000) found indications of preference for canopy flight for some taxa from the superfamily Geometroidea in a lowland tropical forest in Malaysia; Schulze et al (2001) found different assemblages of Sphingidae and Erebidae (Arctiinae) at canopy level in comparison with the ground level in Borneo; Brehm (2007) found that canopy assamblages of tropical rain forest in Costa Rica were dominated by Erebidae, whereas Geometridae were more abundant in the understorey level; Ashton et al (2015) found a clear, but variable, vertical stratification in moth assemblages regardless of elevation and latitude. But, it is hard to compare the situation in tropical areas with temperate regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, with very few exceptions (e.g. Kessler et al ., ; Ashton et al ., ; Szewczyk & McCain, ), multi‐gradient analyses for the same taxonomic group, allowing comparisons of elevational richness patterns across biogeographical realms and tests for general predictors, remain restricted to vertebrate taxa (McCain & Grytnes, , and references therein). For vertebrates, strong climatic drivers are empirically supported, but conclusions vary by taxon.…”
Section: Introductionmentioning
confidence: 99%